Enterprise Integration Architecture and Capabilities of SAP S/4HANA: A Technical Overview - Prahlad Reddy Devireddy, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the evolution and capabilities of SAP S/4HANA's enterprise integration architecture, focusing on its transformative impact across various organizational dimensions. The article explores the fundamental architectural components, integration technologies, data management approaches, and security frameworks that constitute modern enterprise systems. It investigates how cloud-native principles, artificial intelligence, and machine learning are reshaping integration strategies while addressing the challenges of hybrid and multi-cloud environments. The article delves into implementation methodologies, best practices, and emerging patterns in enterprise integration, highlighting the significance of pre-built components and automated development approaches. Through detailed analysis of industry-specific scenarios and case studies, this paper demonstrates how organizations across different sectors are leveraging SAP S/4HANA's capabilities to achieve digital transformation objectives. The article also examines future trends and technological advancements that are likely to influence the evolution of enterprise integration architecture, providing insights into the potential impact of quantum computing, edge computing, and immersive technologies on business operations.
Keywords: Enterprise Integration Architecture; SAP S/4HANA; Cloud-Native Integration; Digital Transformation; Enterprise Data Management